(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The object of the study includes the phraseological units with the component “eye” which used in the story “The Death of the Usurer” by S. Ayni. Through specific examples from the story, the research investigates these units’ linguistic and cultural characteristics. Employing methods such as descriptive, comparative, and componential analysis, the study explores the semantic characteristics of the selected phraseological units.